Mechanism of CaO catalyst deactivation with unconventional monitoring method for glycerol carbonate production via transesterification of glycerol with dimethyl carbonate. (15th September 2021) - Praikaew, Wanichaya; Kiatkittipong, Worapon; Aiouache, Farid; Najdanovic‐Visak, Vesna; Termtanun, Mutsee; Lim, Jun Wei; Lam, Su Shiung; Kiatkittipong, Kunlanan; Laosiripojana, Navadol; Boonyasuwat, Sunya; Assabumrungrat, Suttichai
Summary: Glycerol carbonate (GC) was synthesized by transesterification of glycerol with dimethyl carbonate (DMC) using calcium oxide (CaO) derived from eggshell as a catalyst. The best results of 96% glycerol conversion and 94% GC yield were achieved under the following reaction conditions: 0.08 mole ratio of CaO to glycerol, 1:2.5 mole ratio of glycerol to DMC, 60°C reaction temperature, and 3 hours reaction time. As expected, CaO showed deteriorated catalytic performance when recycling as observed by a rapid decrease in GC yield. This research showed that the active CaO phase first was converted to calcium methoxide (Ca[OCH3 ]2 ) and calcium diglyceroxide (Ca[C3 H7 O3 ]2 ) and finally to carbonate phase (CaCO3 ) which can be confirmed by XRD patterns. According to the phase transformation, the basicity decreased from 0.482 mmol/g to 0.023 mmol/g, and basic strength altered from strong basic strength (15.0 < H_ < 18.4) to weak basic strength (7.2 < H_ < 9.8), resulting in the lower catalytic activity of the consecutive runs. Despite the fact that the GC selectivity was almost 100%, the reaction products (methanol and GC) were not obtained in their stoichiometric ratio and their extents corresponded with that of the catalyst phase transformation to CaCO3 . The mechanism of CaO catalyzed transesterification based on the condensation reaction of glycerol and catalyst was proposed, and in situ formation of water‐derivative species was hypothesized as a cause of CaO transformation. CaO could react with DMC and water, generating methanol and CaCO3 . This enabled unconventional monitoring of catalyst deactivation by checking if the mole ratio of methanol to GC was higher than 2:1 of its reaction stoichiometric ratio. It was also demonstrated that calcination of post‐run catalyst at 900°C to CaO exhibited almost constant catalytic activity, and the mole ratio of methanol to GC was constant at its reaction stoichiometry (2:1) for at least 4 times use. Abstract : The originally proposed reaction mechanism can be related and evidenced by the cause of the catalyst deactivation. Observing methanol by‐product over stoichiometric ratio indicates the catalyst deactivation. CaO phase change caused by in situ formation of water‐related species. The deactivation mechanism of CaO was proposed in this research.